The complete nucleotide sequence of the glnALG operon of Escherichia coli K12. - Miranda-Ríos, J (1987)
The nucleotide sequence of the E. coli glnALG operon has been determined. The glnL (ntrB) and glnG (ntrC) genes present a high homology, at the nucleotide and aminoacid levels, with the corresponding genes of Klebsiella pneumoniae. The predicted aminoacid sequence for glutamine synthetase allowed us to locate some of the enzyme domains. The structure of this operon is discussed.